2002
DOI: 10.1023/a:1021009418421
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The following biomarkers were investigated in stream populations of juvenile brown trout (Salmo trutta f. fario) and gammarids (Gammarus pulex) to determine if crayfish mortality could have been confounded by pollutants: (1) alterations of fish liver ultrastructure, (2) fish gill and kidney histopathology, (3) stress protein (hsp70) expression in fish liver and gills and in gammarids, and (4) changes in various blood parameters of brown trout. In addition, the following measurements were conducted in parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The observed result was supported by a previous study which reported that the contaminant release was associated with the altered HSP70 expression levels in the liver and gill of the cray fish living in the polluted stream system (Triebskorn et al 2002). On further analysis of the results obtained, the mtHSP70 level in the Ennore estuary fish showed a significant seasonal variation (33% increase) when compared to Kovalam estuary sample which shows only 24% increase during summer season.…”
Section: Discussionsupporting
confidence: 84%
“…The observed result was supported by a previous study which reported that the contaminant release was associated with the altered HSP70 expression levels in the liver and gill of the cray fish living in the polluted stream system (Triebskorn et al 2002). On further analysis of the results obtained, the mtHSP70 level in the Ennore estuary fish showed a significant seasonal variation (33% increase) when compared to Kovalam estuary sample which shows only 24% increase during summer season.…”
Section: Discussionsupporting
confidence: 84%
“…Apart from the synergistic effects of toxicants, environmental factors such as temperature (Figure 5) [103], salinity [104], and oxygen supply [105] also influence the expression of HSPs and may also have a synergistic effect in combination with toxicants, thus making their consideration as biomarkers doubtful. For example, Cd exposure increased the HSP70 concentrations in marine clams, whereas salinity markedly lowered the same level in that species.…”
Section: Discussion: Critical Analysismentioning
confidence: 99%
“…These results qualify HSP70 as a biomonitor for environmental pollution provided that essential environmental parameters such as pH and temperature are kept constant [108]. Apart from temperature and pH, much similar emphasis has also been placed on the analysis of nutrients, electrolytes, and dissolved oxygen content [105]. …”
Section: Discussion: Critical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Among the NCSR components, high attention was given to the antioxidant enzymes (Almeida et al, 2002), heat shock proteins, such as HSP70 (Triebskorn et al, 2002), lipid and fatty acid composition (Bergé & Barnathan, 2005), lipid peroxidation products (Valavanidis et al, 2006), enzymes and products involved in energy metabolism including anaerobiosis (Almeida et al, 2002), gene expression (Lee et al, 2008), etc.…”
Section: Introductionmentioning
confidence: 99%